Part (1):
The graph is shown in the attached image.
As we can note from the graph, the solution of the system of equations is indicated by the point of intersection between the two lines which is (6,-2)
Part (2):
The equations given are as follows:
2x + 3y = 6 ...........> equation I
x - 2y = 10
which can be rewritten as:
x = 2y + 10 ...........> equation II
Substitute with equation II in equation I and solve for y as follows:
2x + 3y = 6
2(2y+10) + 3y = 6
4y + 20 + 3y = 6
7y = 6 - 20
7y = -14
y = -2
Substitute with y in equation II to get x as follows:
x = 10 + 2y
x = 10 + 2(-2)
x = 10 - 4
x = 6
The solution is (6,-2)
Part (3):
The equations given are:
2x + 3y = 6 .............> equation I
x - 2y = 10 ...........> equation II
Multiply equation II by -2, this will give:
-2x + 4y = -20 ............> equation III
Add equation I and equation III as follows:
2x + 3y = 6
+ -2x + 4y = -20
.........................................
0x + 7y = -14
7y = -14
y = -2
Substitute with y in equation II to get x as follows:
x - 2y = 10
x - 2(-2) = 10
x + 4 = 10
x = 10 - 4
x = 6
The solution is (6,-2)
Hope this helps :)